Differences in the prevalence of sarcopenia in peritoneal dialysis patients using hand grip strength and appendicular lean mass: Depends upon guideline definitions - Asmat Abro (2018)
© 2018 Macmillan Publishers Limited, part of Springer Nature. Background: Peritoneal dialysis (PD) patients with sarcopenia have increased risk of mortality. There is consensus that sarcopenia should combine assessments of muscle function and mass. We wished to determine the effect of using different operational definitions in PD patients. Methods: Hand grip strength (HGS) and segmental bioimpedance derived appendicular lean mass (ALM) were measured and the prevalence of sarcopenia determined using the Foundation for the National Institutes of Health Sarcopenia Project (FNIH), European Working Group on Sarcopenia Older Persons (EWGSOP), and Asian Working Group on Sarcopenia (AWGS) definitions. Results: We studied 155 PD patients, 95 men (61.3%), mean age 63.0 ± 14.9 years, 37.4% diabetic, treated by PD 9 (3-20) months with a HGS of 22.5 (15.5-30.2) kg, weight 73.6 ± 16.6 kg, % body fat 31.4 ± 4.2, and ALM index 7.52 ± 1.40 kg/m2. More patients were defined with muscle weakness using the EWGSOP compared to the FNIH criteria (X2= 6.8, p = 0.009), whereas fewer patients met the EWGSOP criteria for muscle wasting compared to FNIH body mass index adjustment (X2= 7.7, p = 0.006). However, when combining both criteria, there was no difference in the prevalence of sarcopenia between the different recommended definitions (11-15.5%). Conclusion: We report a much lower prevalence of sarcopenia compared to studies in haemodialysis patients. Although there may be an element of patient selection bias, PD patients are not subject to changes in hydration and electrolytes with haemodialysis, which can affect HGS and muscle mass measurements. Using HGS and segmental bioimpedance we found similar prevalence of sarcopenia using EWGSOP, FNIH, AWGS definitions.